Education Inequality Revisited Through the Lived Experiences of Parents During Virtual Learning - Ghamrawi, Norma; Shal, Tarek; Machmouchi, Ikram; Ghamrawi, Najah (Advances in Social Sciences Research Journal, 2020)
The purpose of this study was to investigate the lived experiences of parents who providing support for their children during virtual learning to better understand whether virtual learning was potentially exacerbating or soothing access of children of various socio-economic statuses to education. For this purpose, an online survey was passed into all e-channels of parents of children enrolled in primary schools accessible by the researchers. A total of 87 respondents constituted the research sample. Quantitative data was analyzed using SPSS 21.0 for windows, while qualitative data was analyzed using thematic analysis. Post to this, 3 e-focus group interviews were held with a total of 18 parents who volunteered to participate to better understand their view points. Findings show that parents are highly frustrated in relation to virtual schooling offered to their children. The underlying reasons for such exasperation have been attributed to the time that it requires them to put into their children learning; the money they needed to spend on technology; the lack of proficiency they suffered from using digital technologies; the preparedness of their children’s teachers in terms of using technologies; the competency of their children using digital technologies; and the internet connectivity in the country. It can be therefore concluded that student access to education in light of Covid-19 is getting more linked to higher levels of socio-economic statuses thus advancing education inequality even more.